Analisis Kejadian Karies Gigi Pada Anak SD Al-Azhar di Kelurahan Bangun Jaya Kota Pagar Alam - Mariyam Jamilah; Lilis Suryani,; Chairil Zaman (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2022)
Dental caries is a disease that often occurs in children, which is a condition of cavities and causes pain. This study aims to determine the factors associated with the incidence of dental caries in elementary students at Al-Azhar Elementary School, Pagar Alam City Donation Work Area in 2021. The design of this study used a Cross Sectional, where the population in this study were students of Al-Azhar Elementary School in Bangun Village. Jaya Kota Pagar Alam in 2021. The method for taking the sample in this research is the total sampling technique. The research sample is Al-Azhar Elementary School students in Bangun Jaya Village, Pagar Alam City in 2021, each with 97 respondents. This research has been carried out in June 2021. Data collection using a questionnaire. The results of statistical test analysis using the Chi-Square statistical test where the results show there is a significant relationship (p < 0.05) for the attitude variable (p value 0.008) and toothbrushing habits (p value 0.02). dominant is attitude (p value 0.012) with OR value (0.162). From this study it was concluded that the Puskesmas should optimize dental and oral health services in preventing caries as early as possible in children